Breeding and end‑use quality traits of roots, tubers, and bananas (RTB) crops for authentic African cuisines—a review - Alamu, E.O.; Adesokan, M.; Awoyale, W.; Maziya-Dixon, B. (Springer, 2024)
The breeding of improved varieties of root, tuber, and banana (RTB) crops has led to the release of several varieties with excellent agronomic performances, such as high yield and disease resistance. However, farmers and end users have hampered the adoption of these improved varieties of RTB crops over the years due to their processing capacity and final product quality. Across the RTB crops, the key quality and adoption criteria differ for different products. The vital quality traits that can enhance the adoption of these improved varieties have been identified for cassava, yam, and banana/plantain. Some significant traits cassava farmers and consumers prefer are early-bulking, non-bitter roots, in-ground storability, drought tolerance, good pounding capabilities, and excellent cooking and sensory qualities. The acceptance of improved yam varieties is driven by good yield, resistance to pests, good cooking quality, and admirable textural attributes for both boiled and pounded yams. Also, for banana/plantain Musa spp., farmers and end users prefer varieties with appealing sensory properties and good agronomic attributes. Farmers’ and end-users’ most desired traits are high yields, good cooking qualities, and climate resilience. Though the quantification of some of these quality traits is challenging, the synergized work of breeders and food scientists with the use of standardized protocols during the breeding, selection, and evaluation stages will enhance the production of cultivars that will meet the preferences of all stakeholders along the food product value chain of the RTB crops.